Value Addition of Traditional Indian Dairy Products Using Herbs and Spices- An Overview - Maji, Soma; Bumbadiya, Mitul; Sao, Khushbu (International Journal of Bio-resource and Stress Management, 2023)
Natural antioxidants have positive effects on human well-being and various conditions of disease, such as cardiovascular diseases, neurodegenerative diseases, diabetes and cancer. They have been attributed to several of their biological activity to scavenge reactionary oxygen species (ROS) with oxidative stress. Herbs and spices are the rich source of natural antioxidants. They also contain many phytochemicals (tannins, flavonoids, alkaloids), essential oils, phenols, saponins, vitamins and micro and macro minerals. They play a great role in food system as flavourings, antioxidant, preservative and also possess medicinal property. Milk products are the most promising and fascinating foods due to their potential antioxidant activities. To extend the shelf life and nutrition value of dairy products specially fermented dairy products, few herbs are very helpful owing to their antifungal and antibacterial effect. Traditional Indian dairy products such as paneer, chhana, sandesh, dahi, lassi, ghee, butter and so on are the most commonly consumed food in Indian. It is well known that, milk and milk products are the most promising and compatible vehicle for delivering nutritional, functional health benefits of different herbs and spices. In this short review use of some of the important herbs and spices in traditional Indian dairy products has been dealt. Fortification of different herbs and spices in dairy products strengthens their nutritional and therapeutic values. It also enables the development of value-added dairy products.